Performance Evaluation of Exclusive Bus Lane System using Simulation-based Analysis - A Case Study of a Section in Kathmandu-Bhaktapur Route during Morning Peak Hour - Acharya, Samrat; Marsani, Anil (International Journal on Engineering Technology and Infrastructure Development, 2026)
In developing cities with heterogeneous vehicle composition and limited road space, such as Kathmandu, urban roads are becoming highly congested, especially the major corridors like the Kathmandu-Bhaktapur Road. This study aims to examine whether exclusive bus lanes and signal priority system can be effectively implemented in such an environment. A microsimulation model was developed using PTV VISSIM replicating existing traffic conditions on which various scenarios involving exclusive bus lanes and signal priority were simulated for morning peak hour where performance indicators like queue length and travel time were analyzed. Introduction of exclusive bus lanes prioritizes public transport by providing separate lane, but it heavily penalizes general traffic by amplifying the queue in the normal lanes. Signal priority when used with EBLs eliminates queues in bus lanes to minimal level while also softening the negative impact on normal lanes. Similarly, the travel time of public transport reduces by 7-13% after the introduction of exclusive bus lanes, but delivers the biggest improvement in both directions when used in conjunction with signal priority, resulting the reduction of 20-23%. In contrast, EBL implementation increased travel time for vehicles in normal lanes; however, the increase was substantially reduced when combined with signal priority, dropping from +21% to -13% in the Tinkune-Lokanthali approach and from +98% to +67% in the Lokanthali-Tinkune approach. Hence, highlighting the effectiveness of exclusive bus lane system with signal priority for the Kathmandu-Bhaktapur Route.